Determinants of eco-halal products consumption pattern among generation MZ: a literature review / Nawal Esa Yazid Esa ... [et al.] - Yazid Esa, Nawal Esa; Ahmad, Nurul Afiqah; Haron, Hazliza; Abdul Rahman, Azura (Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi MARA (UiTM), 2024)
This research study examines the effects of product information transparency, attitude, health consciousness, eco-literacy, and religiosity on eco-Halal product consumption patterns, with lifestyle as a mediator. The study explored the literature review of the interrelationships between these variables and their collective impact on consumer behaviour in the context of eco-Halal consumption. This research targets consumers from Generation MZ, or the combination of Millennials and Generation Z, encompassing individuals born between the early 1980s and mid-2000s. These two generations are selected due to their demographic significance. Understanding their characteristics, values, and behaviours is crucial for effective targeting by marketers, policymakers, and businesses. The MZ generation exhibits distinct values and attitudes compared to previous generations, with significant social and cultural shifts. The method of this study involves extracting data (articles) from three prominent databases (Scopus, Web of Science, and Google Scholar) subscribed by UiTM. Then, research is carried out by reading and analysing about 20 journal articles to understand concepts, opinions, and experiences. The findings reveal the significance of product information transparency, attitude, health consciousness, eco-literacy, and religiosity on eco-Halal product consumption patterns. The lifestyle as a mediator is investigated to determine if it strengthens, weakens, or has no significance for eco-Halal product consumption patterns. The results from the literature review highlight the complex interplay between product information transparency, attitude, health consciousness, eco-literacy, religiosity, and lifestyle in shaping eco-Halal consumption patterns. The findings are expected to provide valuable insights for researchers, businesses, marketers, and policymakers in understanding the factors that drive consumer behaviour in this domain. Recommendations include stakeholders considering significant factors and developing targeted strategies to promote eco-Halal products and foster a sustainable and ethical marketplace that complies with Islamic values.